Handbook of women Biblical interpreters : a historical and biographical guide - Taylor, Marion Ann.; Choi, Agnes (Grand Rapids, Mich. : Baker Academic, 2012)
"The history of women interpreters of the Bible is a neglected area of study. Marion Taylor presents a one-volume reference tool that introduces readers to a wide array of women interpreters of the Bible from the entire history of Christianity, from the early church to the twenty-first century. Her research has implications for understanding biblical interpretation--especially the history of interpretation--and influencing contemporary study of women and the Bible. Contributions by over 125 top scholars introduce foremothers of the faith who address issues of interpretation that continue to be relevant to faith communities today, such as women's roles in the church and synagogue and the idea of religious feminism. Women's interpretations also raise awareness about differences in the ways women and men may read the Scriptures in light of differences in their life experiences. This text will prove useful to students, scholars, and pastors, who will be inspired, provoked, and challenged by the women introduced in the handbook. It will also provide a foundation for further detailed research and analysis. Some of the interpreters referenced include: Elizabeth Rice Achtemeier; Birgitta of Sweden; Catherine Mumford Booth; Anne Bradstreet; Catherine of Siena; Clare of Assisi; Egeria; Elizabeth I; Hildegard of Bingen; Julian of Norwich; Thrs¨e of Lisieux; Marcella; Henrietta C. Mears; Florence Nightingale; Phoebe Palmer; Faltonia Betitia Proba; Pandita Ramabai; Christina Georgina Rossetti; Dorothy Leigh Sayers; Elizabeth Cady Stanton; Harriet Beecher Stowe; Teresa of Avila; Sojourner Truth; Susanna Wesley" -- Publisher description.
Includes bibliographical references and indexes.
Keywords: Women Biblical scholars; Bible -- Criticism, interpretation, etc. -- History